A study on growth, instability and direction of chilli trade in India - V A Ramachandra, R A Yeledhalli, N Ashoka, C Kuldeep (Journal of Spices and Aromatic Crops, 2013)
This study was aimed at studying growth, instability in area, production and productivity and direction of trade of chilli from India. Compound growth rate analysis, Instability analysis and Markov chain analytical tools were used for the study. The results indicated that the growth in area under chilli was negative, while production showed increasing growth due to increased productivity. The sources of instability in chilli production were found to be change in area variance and change in yield variance. Malaysia, Sri Lanka, United Arab Emirates and Indonesia were found to be the loyal markets for Indian chillies. The influence of export price and production on the changes in export of chilli was positive, but the influence of domestic price was negative.